2011
DOI: 10.1089/scd.2011.0091
|View full text |Cite
|
Sign up to set email alerts
|

Improved Efficiency of Female Germline Stem Cell Purification Using Fragilis-Based Magnetic Bead Sorting

Abstract: The enrichment of female germline stem cells (FGSCs) and the establishment of cell lines are influenced by the efficiency of cell purification. A previous study using mouse vasa homolog (MVH)-magnetic bead sorting for the isolation and purification of mouse FGSCs showed a relatively low efficiency. In this study, we tested 3 further proteins with the aim of improving the efficiency of FGSC purification. Immunofluorescence assays and magnetic sorting were performed using short-type pituitary gland and brain-cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
95
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 21 publications
5
95
1
Order By: Relevance
“…These results showed that, under identical culture conditions as those reported by Zou et al (5, 7), the Ddx4-expressing cells from postnatal mouse ovaries did not enter mitosis during the 72-h cell culture. This is in contrast to the previous report that isolated FGSCs from the DDX-4 antibody-based purification started to proliferate within 24 h after seeding (7).…”
Section: Ddx4-expressing Cells From Postnatal Mouse Ovaries Are Mitotcontrasting
confidence: 99%
See 4 more Smart Citations
“…These results showed that, under identical culture conditions as those reported by Zou et al (5, 7), the Ddx4-expressing cells from postnatal mouse ovaries did not enter mitosis during the 72-h cell culture. This is in contrast to the previous report that isolated FGSCs from the DDX-4 antibody-based purification started to proliferate within 24 h after seeding (7).…”
Section: Ddx4-expressing Cells From Postnatal Mouse Ovaries Are Mitotcontrasting
confidence: 99%
“…To evaluate the proliferation of Ddx4-expressing cells over a prolonged period, we cultured and passed the above-mentioned primary cells, as described by Zou et al (5,7). We found that the cultured testicular cells, as a positive control, formed RFP-positive cell colonies after 5-8 d of in vitro culture (Fig.…”
Section: Ddx4-expressing Cells From Postnatal Mouse Ovaries Are Mitotmentioning
confidence: 94%
See 3 more Smart Citations